Anti-crack concrete for highway construction and preparation method thereof
By using low-heat cement, specific admixtures and degradable repair microspheres in crack-resistant concrete, the problems of high cost, complex construction, low compression resistance and insufficient environmental performance of existing crack-resistant concrete are solved, and efficient, environmentally friendly and economical concrete preparation is achieved.
Patent Information
- Application Number
- CN202411908159.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-14
AI Technical Summary
The existing crack-resistant concrete requires high-cost additives in the production process, the construction process is complex, the compressive resistance is low, the maintenance cost is high, and the environmental protection performance is insufficient.
Optimize the choice of chemical composition and aggregates of cement and adopt degradable repair microspheres to achieve self-healing functions, simplify the preparation process and improve environmental performance by using low-heat cement and specific blends such as polymer fibers.
It significantly improves the crack and compressive properties of concrete, reduces maintenance costs, simplifies the construction process, reduces the impact on the environment, and promotes the recycling of resources.
Smart Images

Figure CN119613027A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to anti-cracking concrete for highway construction and a preparation method thereof. Background Art
[0002] Concrete is a kind of artificial stone, which is made of cementitious materials, granular aggregates, water, and admixtures and additives added in a certain proportion, and then mixed evenly, compacted, cured and hardened. It is widely used in civil engineering, including cement as cementitious materials, sand and stone as aggregates; and water (which may contain admixtures and additives) in a certain proportion, and then mixed evenly, compacted, cured and hardened to form artificial stone.
[0003] Anti-crack concrete refers to concrete that has special additives (such as anti-crack agents, water reducers, etc.) added to it or by optimizing the mix ratio to improve its anti-crack performance. It has excellent anti-crack performance and can effectively prevent cracks caused by temperature changes, shrinkage, etc., ensuring the integrity and stability of the building structure.
[0004] The existing crack-resistant concrete has the following disadvantages: in the production process of the existing crack-resistant concrete, it is often necessary to add some special additives and auxiliary materials such as crack control agents. The cost of these materials is relatively high, resulting in a relatively high price for the crack-resistant concrete. This may limit its application for some engineering projects with high cost requirements. In order to give full play to the crack resistance of the crack-resistant concrete, the existing crack-resistant concrete needs to strictly control parameters such as cement slurry ratio and aggregate proportion during the construction process. This requires construction personnel to have a high level of technical skills and rich experience, otherwise it may affect the crack resistance and service life of the concrete. Although the existing crack-resistant concrete performs well in crack resistance, its compressive resistance may be relatively low. Due to the nature of concrete, For heterogeneous materials, the weak link is often located in the interface transition zone between aggregate and cement paste, which may cause the concrete to be damaged when it is under greater pressure. Existing crack-resistant concrete often needs to be repaired manually after cracks appear, which increases maintenance costs and time. The above-mentioned crack-resistant concrete for highway construction achieves self-repairing function by adding degradable repair microspheres, which is significantly better than the existing crack-resistant concrete. Some existing crack-resistant concrete may have a certain impact on the environment during preparation and use, such as emitting harmful substances, generating noise and dust pollution, etc. With the improvement of environmental awareness, the requirements for the environmental performance of concrete materials are also getting higher and higher. Therefore, the environmental performance of existing crack-resistant concrete needs to be improved. Summary of the invention
[0005] The invention aims to provide a crack-resistant concrete for highway construction and a preparation method thereof. The crack-resistant concrete for highway construction and a preparation method thereof can resist cracking: through the carefully selected raw material ratio, especially the use of low-heat cement, and the addition of admixtures such as polymer fiber, polypropylene fiber, etc., the crack resistance of concrete is significantly improved. These admixtures can enhance the toughness of concrete and reduce the occurrence of cracks. The selection of raw materials is optimized: the specific chemical composition of cement, the content of dicalcium acid is not less than 40%, the content of tricalcium aluminate is not more than 6%, the content of free calcium oxide is not more than 1.0%, and the specific surface area is not less than 250m / kg, which ensures the high quality and stability of concrete. The aggregate is strictly selected and cleaned to ensure the uniformity and durability of concrete. Innovative application of degradable repair microspheres: the structural design of the degradable repair microspheres is unique, which can respond quickly when micro gaps are generated in the concrete. The self-repair function is realized by injecting a dissolving liquid to melt the microspheres and fill the gaps. This self-repair mechanism not only improves the durability of concrete, but also reduces maintenance costs. The preparation process Standardization: The preparation process includes raw material preparation, proportioning and weighing, cement, aggregate, water, mixing and mixing of admixture raw materials and additives except degradable repair microspheres, microsphere processing and injection, etc. Each step has been carefully designed and optimized to ensure the quality and performance of concrete. Strict control and standardized operations in the preparation process help improve production efficiency and product consistency. Sample testing and verification: During the preparation process, the concrete is ensured to meet the design requirements by preparing samples and conducting testing and verification. In particular, the effectiveness of degradable repair microspheres is verified by impacting the samples to produce micro-gaps and simulating the repair process. Environmental protection and sustainability: The materials used, such as low-heat cement and degradable repair microspheres, meet environmental protection requirements and reduce the impact on the environment. The use of degradable repair microspheres also promotes the recycling of resources and sustainable development. Construction efficiency and quality control: The preparation method has a high degree of standardization and automation, which helps to improve construction efficiency. Through sample testing and verification, potential quality problems can be discovered and resolved in a timely manner to ensure the quality and safety of highway construction.
[0006] In order to achieve the above effects, the present invention provides the following technical solutions: A crack-resistant concrete for highway construction, comprising the following raw materials in parts by weight: 35-45 parts of cement, 10-15 parts of aggregate, 10-15 parts of water, 10-40 parts of admixture and 5-10 parts of additives.
[0007] Furthermore, the cement is low-heat cement, and the content of dicalcium carbonate in the low-heat cement should be no less than 40%, the content of tricalcium aluminate should not exceed 6%, the content of free calcium oxide should not exceed 1.0%, and the specific surface area should not be less than 250m / kg.
[0008] Furthermore, the aggregate includes coarse aggregate and fine aggregate, the coarse aggregate is crushed stone with a diameter of 5-20 mm, and the fine aggregate is natural river sand with a diameter of 1-5 mm.
[0009] Furthermore, the admixture is at least one of polypropylene monofilament fiber, polypropylene mesh fiber, glass fiber, cellulose ether, calcium sulfoaluminate-calcium oxide expansion agent and degradable repair microspheres.
[0010] Furthermore, the degradable repair microsphere structure includes a protective degradation shell, catalyst particles, dicyclopentadiene and a high-degradability shell, the catalyst particles are peroxyphosphotungsten quaternary ammonium salt, the high-degradability shell is made of poly 3-hydroxyalkanoate, the mixing weight ratio of the protective degradation shell, catalyst particles, dicyclopentadiene and high-degradability shell is 0.8-1.2:0.3-0.7:4-6:1, the catalyst particles are attached to the outer wall of the high-degradability shell, the dicyclopentadiene is filled in the inner wall of the high-degradability shell, the protective degradation shell is sleeved on the outer wall of the high-degradability shell, curly fibers are filled between the protective degradation shell and the high-degradability shell, and the protective degradation shell is made of polylactic acid.
[0011] Furthermore, the mixing weight ratio of the protective degradation shell, the catalyst particles, dicyclopentadiene and the high degradation shell is 1:0.5:5:1.
[0012] Furthermore, the additives include a water reducer, a retarder and a thickener, the water reducer is shortened phenol formaldehyde, the retarder is lignin sulfonate, the thickener is hydroxypropyl methylcellulose, and the weight ratio of the water reducer, the retarder and the thickener is 0.05-1.5:0.2-0.4:0.1-0.3.
[0013] A method for preparing crack-resistant concrete for highway construction, applied to any one of the above-mentioned crack-resistant concrete for highway construction, comprises the following steps: S1. Raw material preparation; S2, raw material ratio and weighing; S3, stirring and mixing cement, aggregate, water, admixture raw materials except degradable repair microspheres and additives; S4. Processing, screening and injection of degradable repair microspheres; S5. Inject the degradable repair microspheres into the concrete, and transport the concrete to the designated location for preparation before pouring; S6. Prepare a measuring mold, inject concrete from a batch into it, obtain multiple samples after solidification, and test the samples; S7, impacting another sample to generate micro gaps, injecting a dissolving liquid into the gaps to melt the degradable repair microspheres, repairing the gaps, and then testing the repaired sample again; S8. After the samples meet the design requirements, prepare the production batch of concrete for highway construction.
[0014] Further, the following steps are included: according to the operating steps in S1, the raw material preparation includes selecting, washing, flushing and screening the aggregate.
[0015] Further, the following steps are included: according to the operating steps in S6, the curing process is consistent with the curing and maintenance steps of highway construction, both of which include plastering, calendering, covering and moisturizing, sprinkling and curing, cutting and filling.
[0016] Further, the method comprises the following steps: according to the operation steps in S7, the dissolving solution is a polylactic acid bio-enzyme dissolving solution.
[0017] The present invention provides a crack-resistant concrete for highway construction and a preparation method thereof, which has the following beneficial effects: (1) Performance crack resistance: The crack resistance of concrete is significantly improved through the careful selection of raw material ratios, especially the use of low-heat cement and the addition of admixtures such as polypropylene fiber. These admixtures can enhance the toughness of concrete and reduce the occurrence of cracks.
[0018] (2) Optimizing raw material selection: The specific chemical composition of cement (dicalcium carbonate content not less than 40%, tricalcium aluminate content not more than 6%, free calcium oxide content not more than 1.0%, and specific surface area not less than 250m / kg) ensures the high quality and stability of concrete. Aggregates are strictly selected and cleaned to ensure the uniformity and durability of concrete.
[0019] (3) Innovative application of degradable repair microspheres: The unique structural design of degradable repair microspheres allows them to respond quickly when micro cracks are generated in concrete. By injecting a dissolving liquid to melt the microspheres and fill the cracks, they can achieve self-repair function. This self-repair mechanism not only improves the durability of concrete, but also reduces maintenance costs.
[0020] (4) Standardization of the preparation process: The preparation process includes multiple steps such as raw material preparation, proportioning and weighing, mixing and mixing of cement, aggregate, water, admixture raw materials and additives except biodegradable repair microspheres, microsphere processing and injection. Each step has been carefully designed and optimized to ensure the quality and performance of concrete. Strict control and standardized operations in the preparation process help improve production efficiency and product consistency.
[0021] (5) Sample testing and verification: During the preparation process, samples were prepared and tested to ensure that the concrete met the design requirements. In particular, the effectiveness of the degradable repair microspheres was verified by impacting the samples to create micro cracks and simulate the repair process.
[0022] (6) Environmental protection and sustainability: The materials used, such as low-heat cement and biodegradable repair microspheres, meet environmental protection requirements and reduce the impact on the environment. The use of biodegradable repair microspheres also promotes the recycling of resources and sustainable development.
[0023] (7) Construction efficiency and quality control: The preparation method is highly standardized and automated, which helps to improve construction efficiency. Through sample testing and verification, potential quality problems can be discovered and resolved in a timely manner, ensuring the quality and safety of highway construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention is a schematic flow diagram of a crack-resistant concrete for highway construction and a preparation method thereof. DETAILED DESCRIPTION
[0025] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0026] The present invention provides a technical solution: Example 1, please refer to Figure 1 A crack-resistant concrete for highway construction comprises the following raw materials in parts by weight: 40 parts of cement, 12 parts of aggregate, 12 parts of water, 25 parts of admixture and 7 parts of additives, wherein the cement is low-heat cement, the content of dicalcium sulfate in the low-heat cement should be not less than 40%, the content of tricalcium aluminate should not exceed 6%, the content of free calcium oxide should not exceed 1.0%, and the specific surface area should not be less than 250m / kg, the aggregate comprises coarse aggregate and fine aggregate, the coarse aggregate is crushed stone with a diameter of 5-20 mm, the fine aggregate is natural river sand with a diameter of 1-5 mm, the admixture comprises polypropylene monofilament fiber, polypropylene mesh fiber, glass fiber, cellulose ether, calcium sulfoaluminate-calcium oxide expansion agent and degradable repair microspheres, wherein the mixing weight ratio of the components in the admixture is 1:10:30:50:5:2.
[0027] The degradable repair microsphere structure includes a protective degradation shell, catalyst particles, dicyclopentadiene and a high-degradability shell. The catalyst particles are peroxyphosphotungsten quaternary ammonium salt, and the high-degradability shell is made of poly 3-hydroxyalkanoate. The mixing weight ratio of the protective degradation shell, catalyst particles, dicyclopentadiene and high-degradability shell is 1:0.5:5:1. The catalyst particles are attached to the outer wall of the high-degradability shell, dicyclopentadiene is filled in the inner wall of the high-degradability shell, the protective degradation shell is sleeved on the outer wall of the high-degradability shell, and curly fibers are filled between the protective degradation shell and the high-degradability shell. The protective degradation shell is made of polylactic acid, and the additives include a water reducer, a retarder and a thickener. The water reducer is shortened phenol formaldehyde, the retarder is lignin sulfonate, and the thickener is hydroxypropyl methylcellulose. The weight ratio of the water reducer, the retarder and the thickener is 0.1:0.3:0.15.
[0028] A method for preparing crack-resistant concrete for highway construction, which is applied to any one of the above-mentioned crack-resistant concrete for highway construction, comprises the following steps: S1, raw material preparation, which includes selecting, cleaning, flushing and screening aggregates; S2, raw material proportioning and weighing; S3, cement, aggregates, water, admixture raw materials other than degradable repair microspheres and additives are stirred and mixed; S4, degradable repair microspheres are processed, screened and injected; S5, the degradable repair microspheres are injected into the concrete, and the concrete is transported to a designated location for preparation before pouring; S6 , prepare the measuring mold, inject the concrete from a batch, and obtain multiple samples after solidification. The samples are tested. The solidification process is consistent with the curing and maintenance steps of highway construction, including plastering, calendering, covering and moisturizing, watering and maintenance, cutting and filling. S7, impact another sample to produce micro-gap, inject dissolving liquid into the gap, melt the degradable repair microspheres, repair the gap, and test the repaired sample again. The dissolving liquid is polylactic acid bio-enzyme dissolving liquid. S8, after the sample meets the design requirements, prepare to produce batches of concrete for highway construction.
[0029] Example 2, please refer to Figure 1 A crack-resistant concrete for highway construction comprises the following raw materials in parts by weight: 40 parts of cement, 12 parts of aggregate, 12 parts of water, 25 parts of admixture and 7 parts of additives. The cement is low-heat cement. The content of dicalcium phosphate in the low-heat cement should be not less than 40%, the content of tricalcium aluminate should not exceed 6%, the content of free calcium oxide should not exceed 1.0%, and the specific surface area should not be less than 250m3 / kg. The aggregate comprises coarse aggregate and fine aggregate. The coarse aggregate is crushed stone with a diameter of 5-20 mm, and the fine aggregate is natural river sand with a diameter of 1-5 mm.
[0030] The admixtures are glass fiber, cellulose ether, calcium sulfoaluminate-calcium oxide expansion agent and degradable repair microspheres, wherein the mixing weight ratio of the components in the admixture is 30:50:5:2, and the additives include water reducer, retarder and thickener. The water reducer is shortened phenol formaldehyde, the retarder is lignin sulfonate, the thickener is hydroxypropyl methylcellulose, and the weight ratio of the water reducer, retarder and thickener is 0.1:0.3:0.15.
[0031] A method for preparing crack-resistant concrete for highway construction, which is applied to any one of the above-mentioned crack-resistant concrete for highway construction, comprises the following steps: S1, raw material preparation, which includes selecting, cleaning, flushing and screening aggregates, S2, raw material proportioning and weighing, S3, cement, aggregates, water, admixture raw materials other than degradable repair microspheres and additives are stirred and mixed, S4, a substitute for degradable repair microspheres, polylactic acid balls of equal size are injected, S5, the polylactic acid balls are injected into the concrete, and the concrete is transported to a designated location for preparation before pouring , S6. Prepare the measuring mold and inject the concrete from a batch. After solidification, obtain multiple samples and test the samples. The solidification process is consistent with the curing and maintenance steps of highway construction, including plastering, calendering, covering and moisturizing, watering and curing, cutting and filling. S7. Impact another sample to produce micro-gaps. Inject dissolving liquid into the gaps to melt the polylactic acid balls. After repairing the gaps, test the repaired samples again. The dissolving liquid is polylactic acid bio-enzyme dissolving liquid. S8. After the samples meet the design requirements, prepare to produce batches of concrete for highway construction.
[0032] Example 3, please refer to Figure 1 A crack-resistant concrete for highway construction includes the following raw materials in parts by weight: 40 parts of cement, 12 parts of aggregate, 12 parts of water, 25 parts of admixture and 7 parts of additive, wherein the admixture is different from that in Example 1 in that it does not contain degradable repair microspheres. The sample is processed by the method for preparing crack-resistant concrete for highway construction in Example 1, and the data detected by Example 1, Example 2 and Example 3 are compared for detection. The detection items include concrete crack resistance safety factor and concrete ultimate tensile value, wherein the calculation formula of concrete crack resistance safety factor is: Cr=Ft / Vu; The calculation formula of Ft is: Ft=k1×k2×k3×k4×fctd×bw×d; The calculation formula for Vu is: Vu=0.6×bw×d×v, where v is the shear span ratio; In summary, the calculation formula for the safety factor of concrete crack resistance is: Cr=k1×k2×k3×k4×fctd / (0.6×v); Among them, k1, k2, k3, and k4 are coefficients that affect the crack resistance and shear bearing capacity of concrete, fctd is the design value of the tensile strength of concrete, bw is the section width, d is the effective height, and v is the shear span ratio.
[0033] The calculation formula for the ultimate tensile value of concrete is: Formula: εpa=0.5f(1+0.1p)×(10^-4), where d is the influence of the steel bar diameter. This formula is not directly reflected, but the reinforcement ratio p implies the information of the number and diameter of steel bars. εpa: ultimate tensile value of reinforced concrete; f: tensile design strength of concrete (N / mm²); p: cross-section reinforcement ratio (%), for example, if the reinforcement ratio is 0.2%, then p=0.2; Example: If the reinforced concrete raft slab uses concrete strength grade C25, f=1.3N / mm², and reinforcement ratio p=0.35, its ultimate tensile value can be calculated by substituting it into the formula.
[0034] Through the above examples and calculation formulas, the following data are obtained, see Table 1: The embodiment is tested and analyzed, and two different materials of ecological cement are purchased on the market as the first and second groups, and the following data are obtained: Table 1: Safety factor against cracking Ultimate tensile strength of concrete Structural strength Repair effect Construction efficiency Group 1 K1:1.5K2:1.6 0.55×10-4 31.5MPa generally Poor Group 2 K1:1.5K2:1.5 0.58×10-4 31.9MPa generally Poor Example 1 K1:2.0K2:1.9 2.68×10-4 35MPa better Higher Example 2 K1:1.6K2:1.5- 1.58×10-4 33.5MPa generally generally Example 3 K1: 1.5. K2: 1.4 1.55×10-4 31.5MPa generally Poor According to the data in the above table, it can be concluded that when the embodiments are implemented, the present invention provides a crack-resistant concrete for highway construction and a preparation method thereof. The crack-resistant concrete for highway construction and a preparation method thereof have the following properties: crack resistance: the crack resistance of concrete is significantly improved by carefully selecting the raw material ratio, especially the use of low-heat cement, and the addition of admixtures such as polypropylene monofilament fiber and polypropylene mesh fiber. These admixtures can enhance the toughness of concrete and reduce the occurrence of cracks. The selection of raw materials is optimized: the specific chemical composition of cement (the content of dicalcium acid is not less than 40%, the content of tricalcium aluminate is not more than 6%, the content of free calcium oxide is not more than 1.0%, and the specific surface area is not less than 250m / kg) ensures the high quality and stability of concrete. The aggregate is strictly selected and cleaned to ensure the uniformity and durability of concrete. Innovative application of degradable repair microspheres: the structural design of the degradable repair microspheres is unique, and they can respond quickly when micro gaps are generated in the concrete. The self-repair function is realized by injecting a dissolving liquid to melt the microspheres and fill the gaps. This self-repair mechanism not only improves the durability of concrete, but also reduces maintenance costs.
[0035] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A crack-resistant concrete for highway construction, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of cement, 10-15 parts of aggregate, 10-15 parts of water, 10-40 parts of admixtures and 5-10 parts of additives.
2. The anti-cracking concrete for highway construction according to claim 1, characterized in that: The cement is low-heat cement. The content of dicalcium carbonate in the low-heat cement should be no less than 40%, the content of tricalcium aluminate should not exceed 6%, the content of free calcium oxide should not exceed 1.0%, and the specific surface area should not be less than 250m / kg.
3. The anti-cracking concrete for highway construction according to claim 1, characterized in that: The aggregate includes coarse aggregate and fine aggregate, the coarse aggregate is crushed stone with a diameter of 5-20 mm, and the fine aggregate is natural river sand with a diameter of 1-5 mm.
4. The anti-cracking concrete for highway construction according to claim 1, characterized in that: The admixture is at least one of polypropylene monofilament fiber, polypropylene mesh fiber, glass fiber, cellulose ether, calcium sulfoaluminate-calcium oxide expansion agent and degradable repair microspheres.
5. The anti-cracking concrete for highway construction according to claim 1, characterized in that: The degradable repair microsphere structure comprises a protective degradation shell, catalyst particles, dicyclopentadiene and a high-degradability shell, wherein the catalyst particles are peroxyphosphotungsten quaternary ammonium salt, and the high-degradability shell is made of poly 3-hydroxyalkanoate. The mixing weight ratio of the protective degradation shell, catalyst particles, dicyclopentadiene and high-degradability shell is 0.8-1.2:0.3-0.7:4-6:1, the catalyst particles are attached to the outer wall of the high-degradability shell, the dicyclopentadiene is filled in the inner wall of the high-degradability shell, the protective degradation shell is sleeved on the outer wall of the high-degradability shell, curly fibers are filled between the protective degradation shell and the high-degradability shell, and the protective degradation shell is made of polylactic acid.
6. The anti-cracking concrete for highway construction according to claim 1, characterized in that: The additives include a water reducer, a retarder and a thickener. The water reducer is shortened phenol formaldehyde, the retarder is lignin sulfonate, and the thickener is hydroxypropyl methylcellulose. The weight ratio of the water reducer, the retarder and the thickener is 0.5-1.5:0.2-0.4:0.1-0.
3.
7. A method for preparing crack-resistant concrete for highway construction, characterized in that: The anti-cracking concrete for highway construction as claimed in any one of claims 1 to 6 comprises the following steps: S1. Raw material preparation; S2, raw material ratio and weighing; S3, stirring and mixing cement, aggregate, water, admixture raw materials except degradable repair microspheres and additives; S4. Processing, screening and injection of degradable repair microspheres; S5. Inject the degradable repair microspheres into the concrete, and transport the concrete to the designated location for preparation before pouring; S6. Prepare a measuring mold, inject concrete from a batch into it, obtain multiple samples after solidification, and test the samples; S7, impacting another sample to generate micro gaps, injecting a dissolving liquid into the gaps to melt the degradable repair microspheres, repairing the gaps, and then testing the repaired sample again; S8. After the samples meet the design requirements, prepare the production batch of concrete for highway construction.
8. The process for preparing crack-resistant concrete for highway construction according to claim 7, characterized in that: The following steps are involved: According to the operation steps in S1, the raw material preparation includes selecting, washing, flushing and screening the aggregate.
9. The process for preparing crack-resistant concrete for highway construction according to claim 7, characterized in that: The following steps are involved: According to the operation steps in S6, the curing process is consistent with the curing and maintenance steps of highway construction, and both include plastering, calendering, covering and moisturizing, watering and curing, seam cutting and seam filling.
10. The process for preparing crack-resistant concrete for highway construction according to claim 7, characterized in that: The following steps are involved: According to the operation steps in S7, the dissolving solution is a polylactic acid bio-enzyme dissolving solution.